Anamorelin for patients with cancer cachexia: an integrated analysis of two phase 2, randomised, placebo-controlled, double-blind trials. Issue 1 (January 2015) - Garcia, José M; Boccia, Ralph V; Graham, Charles D; Yan, Ying; Duus, Elizabeth Manning; Allen, Suzan; Friend, John
Summary Background Cancer anorexia-cachexia syndrome is associated with increased morbidity and mortality. Anamorelin is an oral ghrelin-receptor agonist with appetite-enhancing and anabolic activity. We assessed the effects of anamorelin on body composition, strength, quality of life, biochemical markers, and safety in patients with cancer anorexia-cachexia. Methods Data were pooled, a priori, from two completed phase 2, multicentre, placebo-controlled, double-blind trials in patients with advanced or incurable cancer and weight loss of 5% or more. Patients were stratified by weight loss severity (5–15%, >15%) and randomly allocated (1:1) with a computer-generated randomisation schedule to anamorelin hydrochloride 50 mg or placebo once-daily for 12 weeks. Primary outcome was lean body mass by dual-energy x-ray absorptiometry over the 12 week treatment period in eligible patients who had at least one dose of study drug and post-treatment efficacy assessment. We assessed safety in all patients who received at least one dose of study drug. The trials are registered with ClinicalTrials.gov, numbers NCT00219817 and NCT00267358. Findings Between June 29, 2005, and Oct 26, 2006, we enrolled 44 patients in the anamorelin group and 38 patients in the placebo group. 74 patients were eligible for the efficacy analyses. Over 12 weeks, lean body mass increased in 38 patients in the anamorelin group by a least-squares mean of 1·89 kg (95% CI 0·84 to 2·95) compared with a decrease of a least-squares mean of −0·20 kg (−1·23 to 0·83) for 36 patients in the placebo group (difference 2·09 kg [0·94–3·25]; p=0·0006). 42 (95%) of 44 patients treated with anamorelin and 33 (87%) of 38 patients treated with placebo had adverse events. The most common grade 3–4 adverse events (treatment-related or not) in the anamorelin group were fatigue, asthenia, atrial fibrillation, and dyspnoea (two [5%] each); in the placebo group, such events were pneumonia (three [8%]) and anaemia, thrombocytopenia, abdominal pain, anxiety, and dyspnoea (two [5%] each). Interpretation Anamorelin treatment for 12 weeks had a favourable clinical response profile in patients with cancer anorexia-cachexia syndrome. These findings support further investigation in this setting. Funding Helsinn Therapeutics (US), Helsinn Healthcare SA.